Monitoring of livestock Development schemes in sub-Saharan African range areas: The approach of the International Livestock Centre for Africa (ILCA) - Jahnke, Hans E. (Society for Range Management, 1978)
Describes ILCA's monitoring system of African livestock Development schemes in Sub-Sahara range areas, with particular reference to the interdisciplinary exercise of following the important changes of livestock production systems, mentioning conceptual Development, methodological problems & attempted solutions, major dangers & caveats connected w. conceptualization & implementation of monitoring exercises, and expected results.